Donor blood screening and moral responsibility: how safe should blood be?. Issue 3 (11th February 2016) - Verweij, Marcel; Kramer, Koen
Abstract : Some screening tests for donor blood that are used by blood services to prevent transfusion-transmission of infectious diseases offer relatively few health benefits for the resources spent on them. Can good ethical arguments be provided for employing these tests nonetheless? This paper discusses—and ultimately rejects—three such arguments. According to the 'rule of rescue' argument, general standards for cost-effectiveness in healthcare may be ignored when rescuing identifiable individuals. The argument fails in this context, however, because we cannot identify beforehand who will benefit from additional blood screening tests. On the 'imposed risk' argument, general cost-effectiveness standards do not apply when healthcare interventions impose risks on patients. This argument ignores the fact that imposing risks on patients is inevitable in healthcare and that these risks can be countered only within reasonable limits. Finally, the 'manufacturing standard' argument premises that general cost-effectiveness standards do not apply to procedures preventing the contamination of manufactured medical products. We contend that while this argument seems reasonable insofar as commercially manufactured medical products are concerned, publicly funded blood screening tests should respect the standards for general healthcare. We conclude that these particular arguments are unpersuasive, and we offer directions to advance the debate.